Creek Dynamics Determine Pond Subsurface Geochemical Heterogeneity in East Anglian (UK) Salt Marshes - Hutchings, Alec M.; Antler, Gilad; Wilkening, Jean V.; Basu, Anirban; Bradbury, Harold J.; Clegg, Josephine A.; Gorka, Marton; Lin, Chin Yik; Mills, Jennifer V.; Pellerin, Andre; Redeker, Kelly R.; Sun, Xiaole; et al. (Frontiers in Earth Science, 2019)
Salt marshes are complex systems comprising of ephemerally flooded, vegetated platforms hydraulically fed by tidal creeks. Where drainage is poor, formation of saline-water ponds can occur. Within East Anglian (UK) salt marshes, two types of sediment chemistries can be found beneath these ponds; iron-rich sediment, which is characterized by high ferrous iron concentration in subsurface porewaters (up to 2 mM in the upper 30 cm); and sulfide-rich sediment, which is characterized by high porewater sulfide concentrations (up to 8 mM). We present five years of push-core sampling to explore the geochemistry of the porewater in these two types of sediment. We suggest that when carbon is present in quantities sufficient to exhaust the oxygen and iron content within pond sediments, conditions favour the presence of sulfide-rich sediments. In contrast, in pond sediments where oxygen is present—primarily through bioirrigation—reduced iron can be reoxidised and thus recycled for further reduction, favouring the perpetuation of iron-rich sedimentary conditions. We find these pond sediments can alter significantly over an annual timescale. We carried out a drone survey, with ground-truthed measurements, to explore the spatial distribution of geochemistry in these ponds. Our results suggest a pond’s proximity to the creek partially determines the pond subsurface geochemistry with iron-rich ponds tending to be closer to large creeks relative to sulfide-rich ponds. We suggest differences in surface delivery of organic carbon, due to differences in the energy of the ebb flow, or the surface/ subsurface delivery of iron may control the distribution. This could be amplified if tidal inundations flush ponds closer to creeks more frequently, removing carbon and flushing with oxygen. These results suggest that anthropogenic creation of drainage ditches could shift the distribution of iron- and sulfide-rich ponds and thus have an impact on nutrient, trace metal and carbon cycling in salt marsh ecosystems.